Strategy to increase sales of Moringa leaves after the Covid-19 pandemic - Firmansyah, Farid; Sufiyanto, Mohammad Imam; Atha' Mutawalli, Farhad (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
This study aims to determine the strategy to increase sales after the pandemic. The research method is qualitative, using a descriptive type of research. His research background is in one of the private companies in Pekandangan Sangrah, CV Pusaka Madura, especially in using Moringa leaves (Moriga). As for the research results, the impact is to decrypt existing personnel management and provide solutions in increasing post-pandemic sales. The objectives of this study are, 1) Knowing the added value of Moringa leaf flour products, 2) Knowing external internal factors and 3) Knowing strategies that are in accordance with the company's current external internal. The data analysis methods used are quantitative and qualitative analysis. Quantitative analysis is used to determine added value, business development strategies that are prioritized in implementation by CV. Madurese heritage in developing Moringa leaf flour. The three alternative strategies are, 1) Opening business branches in other locations, 2) Expanding marketing and 3) Increasing cooperation with the private sector and related parties. Suggestions for Moringa leaf flour business units are, 1) increasing production and market areas balanced with effective promotion, 2) maintaining the existence of business units in the market with complete infrastructure facilities and promotion with social media, and 3) maintaining and increasing cooperation with related parties